DISCERNMENT ACCORDING TO JOHN CASSIAN AND ITS APPLICATION IN THE USE OF SMARTPHONE FOR CANDIDATES OF PRIESTS - Widodo, Agus; Sasmito, Erwin (Journal of Asian Orientation in Theology, 2024)
The development of digital technology, especially the smartphone, has a tremendous impact within all persons and structures of society, including the seminarians and their formation in seminaries. They can no longer withdraw and refuse to utilize the various facilities or applications provided by smartphone. Instead, they must learn to use it appropriately, wisely and competently, sharpened by appropriate theological insights that reflect priestly spirituality based on a constant dialogue with God. This requires them to have discretionary skills regarding the use of smartphone. Using a quantitative and qualitative methods, this research focuses on the understanding and experience of discretion in using smartphone among the seminarians in Yogyakarta, Indonesia, based on John Cassian’s thoughts on discernment. The result shows that among the seminarians there is a gap between their understanding and their practice on discretion. On the one hand, they understand very well what discretion is and how it should be applied in using smartphone. However, on the other hand, they often do not practice it so they are easily distracted. This research, therefore, recommends that digital discernment skills among seminarians, both personal and communal, need to be continuously improved during their formation years.